2010
DOI: 10.1111/j.1540-5915.2010.00288.x
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Theory of Whistleblowing Intentions: A Benefit‐to‐Cost Differential Perspective*

Abstract: In order to rescue information technology (IT) projects when they go awry, it is critical to understand the factors that affect bad news reporting. Whistleblowing theory holds promise in this regard and a number of salient factors that may influence whistleblowing intentions have been identified. However, an integrative theory that explains how they influence whistleblowing intentions has been conspicuously absent. In this research, we introduce and test a middle-range theory of whistleblowing that can explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
100
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 54 publications
6
100
0
2
Order By: Relevance
“…While age and work experience differed across these two groups, there might be other differences not accounted for in the demographic information collected. Years of work experience, age, and gender have since been found to have significant impact on whistle-blowing intention, where years of work experience and female gender have been positively associated with whistle-blowing intention while age has been negatively associated with whistle-blowing intention (Keil et al, 2010). In our replication, we had similar findings with work experience and age as predictors of reluctance to report to an auditor.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…While age and work experience differed across these two groups, there might be other differences not accounted for in the demographic information collected. Years of work experience, age, and gender have since been found to have significant impact on whistle-blowing intention, where years of work experience and female gender have been positively associated with whistle-blowing intention while age has been negatively associated with whistle-blowing intention (Keil et al, 2010). In our replication, we had similar findings with work experience and age as predictors of reluctance to report to an auditor.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, perceived wrongdoing did not have a significant impact on responsibility to report. Other studies have indicated that more may be at play for an individual assessing whether they ought to report or feel responsible for reporting bad news about an IT project particularly related to organizational climate Keil et al, 2010;Park and Keil, 2009). Perhaps unassessed perceptions about information asymmetry or anonymity (Keil et al, 2010) and how tightly the project was being monitored muted perceptions about project risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Put it simply, when trust has been established, an employee tend to report mishaps which he faced or observed without hesitate or threaten by the reprisal by other party. This in turn increases the benefit-to-cost differential, increasing the likelihood of whistle blowing [33].…”
Section: Resultsmentioning
confidence: 99%
“…When staff members have the impression that effective action will be taken on the basis of their report and this will improve the work climate, peer reporting is more likely. Notwithstanding potential benefits, blowing the whistle on colleagues' misbehaviour often carries high costs, like the risk of retaliation against the reporter (Keil, Tiwana, Sainsbury & Sneha, 2010;Miceli, Rehg, Near & Ryan, 1999). Reducing these costs, by for example offering the possibility to report in an anonymous or confidential way, can promote peer reporting in an individualistic organisational culture.…”
Section: Four Types Of Whistleblowing Policiesmentioning
confidence: 99%